PHYSIOLOGY OF HIGH TEMPERATURE STRESS TOLERANCE AT REPRODUCTIVE STAGES IN MAIZE - S. Naveed; M. Aslam; M. A. Maqbool; S. Bano; Q. U. Zaman; R. M. Ahmad (Journal of Animal and Plant Sciences, 2014)
Maize is a dynamic cereal of world’s agriculture community and is grown both in spring and autumn seasons in Pakistan. In case of spring sowing (February sowing) both pistillate and staminate flowers face high temperature stress and ultimately results in poor seed setting because of increased silk dryness and pollen desiccation. Maize accessions were identified on the basis of their performance at high temperature stress against the indicators like cell membrane thermostability (CMT), leaf temperature (LT), pollen viability %age (PV%), pollen production (PP), pollen germination %age (PG%), pollen grain size (PGS), pollen moisture contents %age (PMC%), and pollen tube length (PTL). Significant differences were observed among the genotypes for high temperature tolerance related indicators which provided wide range of option for selection and opportunity to improve tolerance level against high temperature stress. Principle component analysis (PCA) proved PV%, PP, PG% and PTL as best physiological standards for evaluation of germplasm against high temperature stress. Genotypes viz. B-321, EV-323, POP-209, B-308, B-316, F-127, B-236, EV-340, F-143 and SAWAN-3 showed high level of variability and performed well under heat stress. Genotypes showing high level of adaptability in response to imposed stress could be a good genetic source carrying wide diversity of genes responsible for high temperature tolerance and could be used in breeding program to breed for high temperature tolerance in maize.
Keywords: Maize; high temperature stress; pollen and cell membrane physiology